Wingless eagle : U.S. Army aviation through World War I - Johnson, Herbert Alan (University of North Carolina Press, 2001)
This study asks why the US was so poorly equipped to engage in aerial combat in World War I - despite having been world-leaders in this field 15 years previously. The author looks at the early years of US military aviation to try and ascertain the answer.